PELVIC ROCKING AND ACUPRESSURE POINT Li 4 (Hequ) AGAINST DISMINORE IN CLASS X TEXMACO VOCATIONAL STUDENTS SEMARANG CITY - Vita Triani Adi Puteri Vita; Maftuchah Maftuchah; Ike Saraswati (Jurnal Smart Kebidanan, 2024)
MMenstruation is a natural and physiological process in a woman. In early teens, menstruation sometimes causes fear and worry, because when menstruation comes it is usually accompanied by several complaints, one of which is menstrual pain (dysmenorrhea). One intervention for treating dysmenorrhoea is non-pharmacological management, such as pelvic rocking exercise and Point Li 4 (Hequ) acupressure. Based on the research journal Novi Nur and Yuniati, these two treatments are very effective in reducing pain because they both function to produce endorphin hormones. The aim of this research was to determine the effectiveness of the combination of Lavender Pelvic Rocking Aromatherapy and Li 4 (Hequ) point acupressure in reducing dysmenorrhea pain in class. The results of the research show that the p value = 0.085, which means the value is >0.05, so it can be concluded that there is no significant difference in the effectiveness of pelvic rocking intervention and Li 4 (Hequ) point acupressure combined with lavender aromatherapy in reducing dysmenorrhea pain in class X female students at Texmaco Vocational School. Semarang so Ho was accepted